Orthostatic Responses to Anticholinesterase Inhibition in Persons with SCI - Wecht, Jill M. (Clin Auton Res, 2015)
Acetylcholine (Ach) is the pre-synaptic neurotransmitter of the sympathetic nervous system. Increased pre-synaptic Ach may augment post-synaptic release of norepinephrine thereby increasing systemic blood pressure (BP). The primary objective of this investigation was to determine the hemodynamic effect of pyridostigmine bromide (PYRIDO: 60 mg), an Ach inhibitor (AchI), compared to no-drug (NO-D) during head-up tilt (HUT) in individuals with spinal cord injury (SCI). Secondarily we aimed to determine the effects of PYRIDO compared to NO-D on symptoms of orthostatic intolerance (OI) and adverse event reporting (AE). Ten individuals with SCI (C4–C7) were studied on 2 occasions: visit 1) NO-D and visit 2) PYRIDO. On each visit subjects underwent a progressive HUT maneuver to 15°, 25°, 35° for 5 minutes at each angle and 45 minutes at 45°. Supine and orthostatic heart rate (HR), systolic and diastolic BP (SBP & DBP) were monitored and symptoms of OI and AE recorded. Supine hemodynamics did not differ between the trials. The significant fall in SBP during the NO-D trial was diminished with PYRIDO and five subjects had an increased DBP during HUT with PYRIDO compared to the NO-D trial. Individuals that responded to PYRIDO with an increase in orthostatic BP had significantly lower resting HR than non-responders (p<0.01), which suggests increased levels of pre-synaptic Ach. Subjective symptoms of OI and AE reporting did not differ between the two trials. These preliminary data suggest that PYRIDO is safe and may be effective at ameliorating the orthostatic fall in BP in select individuals with SCI.